Theoretical and Experimental Research of The Stability of The Eccentrically Loaded Steel Columns with Variable Cross–Section - Trusov, Gennady; Ruban, Vladimir (International Journal of Engineering and Technology, 2018)
The article deals with the problem of determining the ultimate load for the eccentrically loaded steel columns with variable-cross section.The purpose of the research work is to offer an evaluation technique and practical calculation of load-bearing ability of the beam-columns with variable cross-section on the basis of numerical research, which will allow to consider the true form of element deflection curve, the effect of cross-section form, physical nonlinearity of the material, and variety of element boundary conditions. The distinctive characteristic of the suggested method is usage of the discrete models for cross-sectional parts, for the true stress-strain curves of the materials, and for the other input data. The method was tested and the results were compared to known theoretical solutions and national standards. To establish the reliability of the developed method, the experimental study of steel columns with variable cross-section was conducted. The suggested method allows to obtain column curves tables of lowering coefficients for these elements, that can be used in practice of civil engineering, and are convenient with national standards and Eurocode.Â